Konstruksi Model Spiritualitas Pastoral bagi Katekis di Era Digital - Wiwin Wiwin; Antonius Denny Firmanto (Jurnal Penelitian Pendidikan Agama Katolik, 2021)
This article aims to build a model of pastoral spirituality that is suitable for catechists in today's digital era. This is important, so that the catechist has a spirit or spirit that is in accordance with his time. In addition, catechists are those who are involved in the work of preaching and accompanying the people. For preaching and pastoral work to be effective, they need a new way of presenting themselves. In an effort to form a model of pastoral spirituality, the author conducted a qualitative research using the documentation method. Data were collected by finding and reading documents and writings that were related to the theme. Then, came the process of analyzing and interpreting the data collected. The result was that the digital age brought within itself both opportunities and challenges for catechists. These challenges demand appropriate models of pastoral spirituality. There are two models of spirituality suitable for the digital era, namely incarnatory pastoral spirituality, and temperance. These two models of spirituality are important, so that God, who is the core of the catechist's preaching, can be understood more by the people. Moreover, thanks to the incarnatory spirit and sophistication, catechists can influence people to have more faith in God.